CFD Modeling of the Effect of Different Surface Texturing Geometries on the Frictional Behavior - Vilhena, Luis M. (2018)
In order to understand the effect of surface texturing parameters on the frictional behavior of textured surfaces and to correlate results of different lubrication regimes, Computational Fluid Dynamics (CFD) numerical analysis of the fluid flow was performed for four different textured surface geometries. The aim of the present research paper is to get theoretical background for the frictional behavior of textured surfaces under hydrodynamic lubrication. Since it is unrealistic to make a direct analysis of a real problem that can possess more than several thousand micro-dimples, the purpose is then to investigate the flow in single cells of periodical micro-dimple patterns and to extract useful conclusions for the lubrication’s framework. Among all geometries studied, optimum geometry shapes in terms of hydrodynamic performance were reported. It was found that the best hydrodynamic performance was achieved with the rectangular geometry (lowest shear force).